Synthesis of CaLa2(MoO4)4:Er3+/Yb3+ Particles by Microwave-Assisted Sol-Gel Method and Their Upconversion Photoluminescence Properties - Sung Lim, Chang (Asian Journal of Chemistry, 2014)
CaLa2(MoO4)4:Er3+/Yb3+ upconversion particles of were successfully synthesized by a microwave-assisted sol-gel method, followed by heat-treatment. Well-crystallized particles formed after heat-treatment at 900 °C for 12 h showed a fine and homogeneous morphology with particle sizes of 1-3 μm. With excitation at 980 nm, the co-doped particles exhibited a strong 525 nm emission band and a weak 550 nm emission band in the green region and a weak 655 nm emission band in the red region. The upconversion intensity of CaLa2(MoO4)4:Er3+/Yb3+# particles was much higher than those of the CaLa2(MoO4)4:Er3+ and CaLa2(MoO4)4:Er3+/Yb3+ particles. The Raman spectra of CaLa2(MoO4)4:Er3+, CaLa2(MoO4)4:Er3+/Yb3+ and CaLa2(MoO4)4:Er3+/Yb3+# particles indicated the detection of additional strong peaks at higher frequencies (1026, 1092 and 1316 cm-1) and weak peaks at lower frequencies (236, 288, 365, 420 and 560 cm-1).